Digitalization in agriculture for innovative transformation in India - Rai, Anil (Indian Farming, 2023)
Digitalization in agriculture has a great potential to bring about significant innovation and transformation in India's agricultural sector. The adoption of digital technologies can help India to increase agricultural productivity, reduce waste, increase agricultural export, increase farmers’ income and improve food and nutrition security. Apart from this, this will help in protecting environment and sustainable development of overall agricultural sector. The increase in internet and mobile phone penetration in India has had a significant impact on various sectors, including agriculture, education, healthcare, and e-commerce. This clearly shows that now Indian agricultural is ready for digital transformation.